2018
DOI: 10.3389/fpls.2018.00650
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis Underlying Correlations Among Growth Duration and Yield Traits Revealed by GWAS in Rice (Oryza sativa L.)

Abstract: Avoidance of disadvantageous genetic correlations among growth duration and yield traits is critical in developing crop varieties that efficiently use light and energy resources and produce high yields. To understand the genetic basis underlying the correlations among heading date and three major yield traits in rice, we investigated the four traits in a diverse and representative core collection of 266 cultivated rice accessions in both long-day and short-day environments, and conducted the genome-wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…It is also interesting to note that several QTLs controlling stalk length (qSL.C6-1, qSL.C6-2) and curd solidity (qCS.C6-1, qCS.C6-4) are probably involved in pleiotropic effects. Similar pleiotropic QTLs were widely found in different species [15][16][17][18]. In cauliflower, co-localizations of QTLs controlling earliness and curd size were also reported, and were considered to be the result of artificial selection for pyramiding these two agronomic traits from different origins [19].…”
Section: Discussionmentioning
confidence: 56%
“…It is also interesting to note that several QTLs controlling stalk length (qSL.C6-1, qSL.C6-2) and curd solidity (qCS.C6-1, qCS.C6-4) are probably involved in pleiotropic effects. Similar pleiotropic QTLs were widely found in different species [15][16][17][18]. In cauliflower, co-localizations of QTLs controlling earliness and curd size were also reported, and were considered to be the result of artificial selection for pyramiding these two agronomic traits from different origins [19].…”
Section: Discussionmentioning
confidence: 56%
“…Co-localized QTLs are important for simultaneous improvement of traits of interest such as grain Fe and Zn concentrations in rice from plant breeder point of view 48 . QTLs controlling correlated traits were usually mapped in the same or close chromosome regions 49 . Some previous studies have reported the phenomenon of QTL co-locations for rice micronutrient concentrations 15,19,23 .…”
Section: Discussionmentioning
confidence: 99%
“…Grain yield is positively correlated with heading date, especially in low latitude areas where the temperature is warm year-round (Gao et al , 2014; Li et al , 2018). In this study, due to continuously high temperature stress during the rice flowering stage in Wuhan, the seed setting rates were significantly decreased; therefore, we analyzed the relationship between heading date and SPP instead of that between heading date and grain yield.…”
Section: Discussionmentioning
confidence: 99%